Framing the Balkans: Everyday Life Beyond Stereotypes (KULT_online, 2019)
The continuous conceptualization of the Balkans as the Other next door to Europe and the persisting tensions in the identities of the peoples inhabiting the area are recurring themes that mark the academic work about this region. Everyday life in the Balkans, edited by David W. Montgomery, a contribution to a subfield that has been neglected for many decades, offers a wide range of topics and views that shed light into how the average Balkan person deals with art, culture, politics, religion, history, livelihood, shifting identities, and neighborly relations in daily life. Covering all the countries of the region, the authors offer insights into what changes the area has undergone in the last decades, including post-socialist and post-war periods, but also keeping an eye on how the past events connect with the modern dynamics of everyday life in the peninsula.